Copyright Ownership of Artificial Intelligence Generated Products - Yang, Liangyu (International Journal of Social Sciences and Public Administration, 2024)
The issue of defining the rights of artificial intelligence generated products has always been a hot topic in various fields, triggering heated academic discussions. The emergence of Chat Gpt has further exacerbated the complexity of the problem.  ChatGPT mainly has powerful abilities such as dialogue comprehension for any task, complex logical reasoning, long grid multi text generation, and automatic generation of program code. Compared to the past where only certain algorithms, rules, and modules were used, ChatGPT has become more advanced, and its models and computational methods are more complex. Especially, its ability to meet the personalized needs of users has led to its generated content being more similar in form to human creative achievements. The definition of its ownership of rights has become more complex.The development of technology will inevitably bring potential for development and legal issues that are difficult to define in the short term.  It is of utmost importance to use the system to regulate newly emerging products in appropriate development channels.In the current state of socio-economic development that emphasizes the protection of rights, especially intellectual property, it is necessary to start from the reality of China and construct a copyright ownership model for artificial intelligence generated products that is suitable for China's active development level and legal system practice.